Strategi Komunikasi Direktorat Pendidikan Profesi Guru Dalam Mengembangkan Minat Generasi Z Menjadi Guru - Claudia, Shintia Ira; Adawiyah, Sa'diyah El (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research aims to analyze the PPG Directorate's communication strategy in developing Generation Z's interest in becoming teachers. The research method used is a qualitative approach with data collection techniques in the form of interviews, observation and documentation. The data collected was analyzed using a process of reduction, presentation and drawing conclusions. The results of the research show that the Directorate of Communication Teacher Professional Education has succeeded in implementing the Communication Strategy to develop Generation Z's interest in becoming teachers with the number of Pre-Service PPG applicants exceeding the target. This is the suggestion obtained from research that the Directorate of Professional Teacher Education can carry out communication strategies to increase registration knowledge in the selection process.